Automatic text summarization using fuzzy c–means clustering - Rahman, A. M. Muntasir; Saleheen, Nasif Noor; Anam, Shakil Ashraful (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.